Health promotion strategies: situational diagnosis in elementary schools - Cristina Berger Fadel; Camila Scheifer Schenberger; Pauline Friederike Warkentin; Márcia Helena Baldani Pinto (Universidade de Fortaleza, 2014)
Objective: To identify the existence of health-promoting actions in public and private schools. Methods: Exploratory and descriptive study with qualitative approach, conducted from June 2012 to June 2013, comprising 10 institutional managers of elementary schools of the public and private networks in the city of Ponta Grossa, PR. Data was collected through semistructured interviews, and examined with use of content analysis thus emerging thematic categories. Results: Regarding nutrition, monitoring is carried out by nutritionists in both types of school. Private schools provide theoretical guidance, while the public ones practice the orientations about personal care. With respect to the access to health services, public schools provide assistance to their students through the city's Health Secretariat, whereas private schools are direct providers. The private network was also found to satisfy fully the human and social development. Concerning the structure, accessibility has been prioritized, both schools having implemented the necessary adaptations. As for security, although schools are equipped with monitoring cameras, violence and vandalism are more frequent in public schools. Conclusion: The institutions practice health-promoting actions, with significant differences between public and private schools, especially in the field of personal care, and social and human development. Approaching public and private networks is suggested, in order to perform an inter-institutional work, aiming to improve health promotion for the students. doi:10.5020/18061230.2014.p169